Forest fire dynamics in Nepal: Regional trends and socio-ecological drivers - Khagendra Prasad Joshi; Susma Giri; Dipesh Kuinkel; Sajesh Kuikel; Rohini Devkota; Dhiraj Pradhananga; Suresh Marahatta; Binod Pokharel (Trees, Forests and People, 2025)
Forest fires pose a significant threat to global ecosystems and communities. In Nepal, the country’s diverse vegetation, climates, and socioeconomic settings contribute to unique regional fire dynamics, which are often underrepresented in national forest fire analyses. This study investigates fire trends, key drivers, and public perceptions of management strategies across Nepal’s four major physiographic regions: the Terai, Chure, Middle Mountains, and High Mountains. We employed remote sensing data, questionnaire surveys (n = 337), and statistical modelling to assess regional fire dynamics and evaluate management approaches. We found that over the past two decades, fire incidents and burned areas have increased significantly in the Chure and Middle Mountains. Broad-leaf deciduous forests in lower regions and needle-leaf forests in higher regions were the most significant contributors. While topographical factors played a major role in most regions, they had minimal influence in the Chure. In the High Mountains, anthropogenic factors—such as proximity to roads and agricultural land cover—were strongly negatively correlated with burned area. Pre-monsoon precipitation consistently showed a significant negative relationship with fire occurrence across all regions, whereas pre-monsoon temperature had no discernible impact. Survey responses highlight strong community support for awareness programs and training, and a widespread belief in the importance of local institutions in fire management. However, labor-intensive fire prevention practices, such as creating fire lines and collecting leaf litter, were less preferred. To mitigate future fire risks, we recommend strengthening community involvement, expanding fire management training, and increasing economic incentives linked to forest resources. These findings offer valuable insights into Nepal’s fire regimes and support evidence-based forest fire management strategies.